Academic Knowledge Production: Framework of Practical Activity in the Context of Transformative Food Studies - Kallio, Galina; Houtbeckers, Eeva (Frontiers in Sustainable Food Systems, 2020)
We have seen an emergence of transformative food studies as part of sustainability transitions. While some scholars have successfully opened up their experiences of pursuing transformation through scholar-activism, assumptions underlying researchers' choices and how scholars orient to and go about their work often remain implicit. In this article, we bring forth a practice theoretical understanding of knowledge production and advocate that researchers turn to examining their own research practice. We ask how to make our own academic knowledge production/research practice more explicit, and why it is important to do so in the context of transformative food studies. To help scholars to reflect on their own research practice, we mobilize the framework of practical activity (FPA). We draw on our own experiences in academia and use our ethnographic studies on self-reliant food production and procurement to illustrate academic knowledge production. Thus this article provides conceptual and methodological tools for reflection on academic research practice and knowledge production. We argue that it is important for researchers to turn to and improve their own academic practice because it advances academic knowledge production in the domain of transformative food studies and beyond. While we position ourselves within the qualitative research tradition, we believe that the insights of this article can be applied more broadly in different research fields and across various methodological approaches.